Installation art in China: a review of Installationskunst in China, transkulturelle Reflexionsräume einer Genealogie des Performativen (Installation art in China, transcultural spaces reflecting a genealogy of the performative), by Birgit Hopfener - Koch, Franziska ([Verlag nicht ermittelt], 2014)
A review of Installationskunst in China. Transkulturelle Reflexionsräume einer Genealogie des Performativen (Installation Art in China. Transcultural ...
Gesehen am 12.05.2020
Keywords: Website